1991
DOI: 10.1007/bf00180985
|View full text |Cite
|
Sign up to set email alerts
|

Polygyny, relatedness and nest founding in the polygynous myrmicine ant Leptothorax acervorum (Hymenoptera; Formicidae)

Abstract: There is high within-nest relatedness for functional queens (with corpora lutea), nonfunctional queens (without corpora lutea), and workers in polygynous nests of Leptothorax acervorum. The high functional queen relatedness suggests that young mated queens are adopted back to their mother nest. Functional queen relatedness does not change with the number of queens present in the nest, suggesting that the number of generations of queens, on average two to three, is rather stable. Worker relatedness decreases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 24 publications
3
27
1
Order By: Relevance
“…(a) Social polymorphism in Leptothorax acervorum The social organization of our studied population strongly contrasts (table 2) with that reported from other polygynous L. acervorum populations (Stille et al 1991;Chan & Bourke 1994;Heinze et al 1995a,b;Bourke et al 1997;Hammond et al 2001Hammond et al , 2006. For example, in a UK population, Hammond et al (2006) showed that in the majority of nests (70% of colonies, n ¼ 17), skew was not significantly different from that expected if all queens reproduced equally.…”
Section: Discussioncontrasting
confidence: 71%
“…(a) Social polymorphism in Leptothorax acervorum The social organization of our studied population strongly contrasts (table 2) with that reported from other polygynous L. acervorum populations (Stille et al 1991;Chan & Bourke 1994;Heinze et al 1995a,b;Bourke et al 1997;Hammond et al 2001Hammond et al , 2006. For example, in a UK population, Hammond et al (2006) showed that in the majority of nests (70% of colonies, n ¼ 17), skew was not significantly different from that expected if all queens reproduced equally.…”
Section: Discussioncontrasting
confidence: 71%
“…In the case of polygynic species, withincolony relatedness is smaller, though it depends on relatedness between the queens (Stille et al, 1991;Ross, 1993). In polygynic colonies a hierarchy between the queens can occur (Ross, 1988;Heinze, 1990;Heinze & Smith, 1990), or a queen multiple mate, not necessarily using the sperm of all males in the same proportion (Ross, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in colonies of all species belonging to the boreal subgenus Leptothorax (sstr.) and in many boreal and alpine L. (Myrafant) several inseminated queens may be present (e.g., Buschinger, 1968;Alloway et al, 1982;Heinze and Buschinger, 1988;Stille et and openly aggressive interactions in early spring, resulting in the formation of rank orders. In each nest only the highest ranking queen began to lay eggs (Heinze and Smith, 1990;Heinze and Lipski, 1990;Heinze and Ortius, 1991).…”
Section: Life Histories Of Boreal Ants: Leptothoraxmentioning
confidence: 99%